TINGKAT PENGETAHUAN DAN SIKAP IBU DALAM KEIKUTSERTAAN PEMERIKSAAN PAP SMEAR - januar dwi christy (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2019)
Introduction: From the data of Petrochemical Hospital from 2017-2018 the percentage of patients undergoing a pap smear examination decreased by 3.7% to 9%. In addition to the preliminary survey of knowledge and attitudes, from 10 mothers found 1 person with good knowledge, 6 people with less knowledge, 3 people with enough knowledge. As for the attitude of the mother found 1 person strongly agrees, 3 people agree, 6 people disagree and 0 people disagree. Based on this problem, it is deemed necessary to conduct research aimed at knowing the description of mothers' knowledge and attitudes in participating in the pap smear examination Method: This study uses descriptive methods. The population is all mothers who come to KKWA Petrokimia Hospital. The sampling used is non-probability sampling (purposive sampling) that is the number of populations being sampled, totaling 86 people. Data obtained from questionnaires and then processed using frequency tables and cross tabulations. Results: The results of the study illustrate that the majority of mothers who came to Pap Pap smear had sufficient knowledge of 51 people (59.30%) and the attitude of disagreement about Pap Smear 46 people (53.49%). Mothers who took a Pap smear because of the doctor's recommendation were 53 people (61.63%). On the advice of the doctor has sufficient knowledge 84.32%, on his own desire has good knowledge 75%, coming on the advice of the doctor has an attitude of disapproval 73.91%, on his own desire has an attitude of agree 59.09%. Discussion: From the results of the study it was concluded that in Petrochemical Hospital, the mother who came to the Pap Smear examination had sufficient knowledge and had a disagreeing attitude towards the Pap Smear examination. Therefore health workers are expected to provide better information about Pap smears and cervical cancer.